Weeds optimally grow in peat swamp after burning - P D Susanti; A Ardhana; R S Wahyuningtyas (Brawijaya University, 2014)
After clearing land by burning the peat, then the weeds and undergrowth will flourish. Even sometimes, the weeds are eventually burned again. Weed is known as a destroyer plant that has to be controlled. Through proper treatment, the existing weeds in peatlands can be potentiallly exploited. The purpose of this study was to determine the calorific value of briquettes as one of peatland weeds utilization. The results showed that the calorific value ranged from 2,492 cal/g to 5,230 cal/g. The lowest calorific value was on ‘teki kecil’ grass (Scirpus grossus Lf), while the highest calorific value was observed for ‘bantalaki grass’ (Hymenachne amplexicaulis Nees). The high calorific value of the peat weeds are potential for biomass briquettes raw materials. The utilization and use of peat weed briquettes as a raw materials expected can reduce land degradation due to peat swamp burning.